Rotating machinery practical solutions to unbalance and misalignment - McMillan, Robert B., 1944- (Fairmont Press ; Marcel Dekker, 2004)
A theoretical and practical understanding of unbalance and misalignment in rotating equipment is presented here. These two conditions account for the vast majority of problems with rotating equipment encountered in the real world.;Numerous examples and so.
Includes index.
Keywords: Balancing of machinery.; Machinery -- Vibration.; elektronické knihy; electronic books